Penerapan Senam Lansia Terhadap Kebugaran Jasmani di Desa Tete B Kecamatan Ampana Tete - Ndama, Metrys; Langitan, Rosamey Elleke; Supetran, I Wayan; Khaira, Nuswatul (Poltekita: Jurnal Pengabdian Masyarakat, 2023)
Aging is a natural process that occurs in every individual throughout his life. One aspect that is closely related to aging is a change in physical fitness. Physical fitness is an important factor that affects the quality of life and well-being of the elderly. The growth rate of the elderly population by the year 2030 is estimated to be greater than the age of adolescents and young people by about 2.1 billion, compared to 2 billion worldwide. The goal of the community dedication is to improve the quality of life of the elderly by improving their physical fitness through the exercise of the elders, because exercising can increase muscle strength and flexibility and thus help them to live a healthier and more fit life in their communities. The activity was carried out in the village of Tete B. Ampana Tete was followed by 15 people, along with 5 people. The results of the activity can be described as follows: all the seniors who attended the gym can follow well and walk smoothly, with no obstacles or injuries. There are three elderly people who have arthritis and hearing loss and are so slow to follow instructions, but they can finish the activity well. The conclusion that can be drawn is that the more frequently doing gymnastics with the elderly, the better the older's health.